1992
DOI: 10.1111/j.1439-0450.1992.tb01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of 3 Probiotics on Experimental Escherichia coli Enterotoxaemia in Weaned Piglets*

Abstract: In this report the efficacy of 3 different probiotics (Bacillus cereus "toyoi", Lactobacillus spp. and Streptococcus faecium) was investigated. They were supplemented in the food of recently weaned piglets that were orally infected with E. coli 0141 K85 ab. Supplementation could not prevent mortality and clinical symptoms nor reduce the faecal excretion of hemolytic E . coli. The possible explanations for the unsatisfying results are various.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 14 publications
0
17
1
Order By: Relevance
“…Administration of lactic acid bacteria has been shown to reduce intestinal coliform and Enterobacteriaceae counts in the majority of previous studies (4,22,24,28,38,39), although some have seen no effects (7,13). The trend towards positive effects observed in ours and other studies, although not significant, should not be ignored, as individual variations in the responses of different animals are to be expected due to the complexity of the intestine (36).…”
Section: Resultscontrasting
confidence: 33%
“…Administration of lactic acid bacteria has been shown to reduce intestinal coliform and Enterobacteriaceae counts in the majority of previous studies (4,22,24,28,38,39), although some have seen no effects (7,13). The trend towards positive effects observed in ours and other studies, although not significant, should not be ignored, as individual variations in the responses of different animals are to be expected due to the complexity of the intestine (36).…”
Section: Resultscontrasting
confidence: 33%
“…Challenge studies with piglets and E. coli 0141 :K85 showed no influence on clinical symptoms, mortality or excre tion of haemolytic E. coli (De Cupere et al, 1992). In a study conducted in our institute, it could also be shown that although the colonization with mucosa-asso ciated enterobacteria was reduced by a probiotic B. cereus preparation (Jadamus et , the probiotic had no influence on the occurrence of pathogenic E. coli as measured with a PCR assay (Goebel et al, 2000).…”
Section: Influence On Intestinal Microbial Communitiesmentioning
confidence: 87%
“…Results are the means of at least three experiments. This decrease in viability may explain the necessity of supplying Bacillus based probiotics in high concentrations and on a daily basis (6). It has been shown that results obtained in vitro highly correlate with those obtained in vivo, thus allowing the use of the formers in the selection of probiotic candidates (10).…”
mentioning
confidence: 88%